HE4u2: work package 1: stocktaking transversal analysis and conclusions - Isabel Menezes (2016)
This Transversal Analysis and Conclusions report is the final deliverable of Work Package 1, "Stocktaking", and includes two main parts: 1. a review of existing literature on teaching and learning strategies for culturally inclusive education in adult and higher education, as well as tools and materials from previous projects' outputs; 2. a collection of examples of good practices, including partners' relevant experiences, synthesise and evaluate existing knowledge through a comprehensive transnational meta-analysis. In the present report the University of Porto has collated and analysed the materials that all the members of the HE4u2 consortium have identified as relevant literature (papers, books, reports) and good practices. Both tasks were supported by specific templates to configure and organize the information (see Appendix 1 and Appendix 2), that the partners filled (see Appendix 3 and Appendix 4) and were instrumental for the analytical work that followed; partners' comments throughout the process were also essential for the conclusion of the analysis. Therefore, this report is the result of the collaborative effort of the various teams.